KUASA KETUA ADAT PADA PROSESI UPACARA ADAT SEREN TAUN (di kasepuhan Cipta Mulya, Kabupaten Sukabumi, Jawa Barat) - Shagita Maulady Anjany; Dade Mahzuni; R.M. Mulyadi (Metahumaniora, 2021)
The title of this article is "The Power of Abah as Customary Leader at the Seren Taun Traditional Ceremony in Kasepuhan Cipta Mulya, Sukabumi Regency, West Java." The purpose of this research is to expose the relevance of Abah's function and power as a traditional leader at the traditional seren taun ceremony, as well as the stages of the traditional seren taun ritual procedure. This study's method is a qualitative research technique that is explained descriptively. Meanwhile, to evaluate this research, the researcher used Foucault and Weber's theory of power, as well as Pierre Bourdieu's theory of habitus, arena, and capital. According to the findings of this study, Abah, as the traditional leader in the execution of the traditional ceremony of seren taun, always uses capital, habitus, and arena in controlling and establishing the smooth functioning of traditional rituals. Abah's power, shown via these three characteristics, enables the phases of the ancient seren taun ritual to be carried out properly and to be passed down from generation to generation to this day. KEYWORDS                                  Seren taun, sukabumi, power, habitus, arena.